2023
DOI: 10.1111/1365-2656.13898
|View full text |Cite
|
Sign up to set email alerts
|

High species turnover and unique plant–pollinator interactions make a hyperdiverse mountain

Abstract: We studied α‐ and β‐diversity of pollinators, flowering plants and plant–pollinator interactions along the altitudinal gradient of Mt. Olympus, a legendary mountain and biodiversity hotspot in Central Greece. We explored 10 study sites located on the north‐eastern slope of the mountain, from 327 to 2596 m a.s.l. Insect surveys were conducted once a month using hand netting (years 2013, 2014 and 2016), and they were combined with recordings of flowering plant diversity (species richness and flower cover). We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
2
3
0
Order By: Relevance
“…Our analysis revealed that the primary driver of beta diversity of interactions was interaction turnover resulting from species turnover ( β ST ), rather than interaction rewiring ( β RW ). This finding is consistent with previous studies conducted on Mount Olympus in Greece (Minachilis et al, 2023) and other spatial gradients (Carstensen et al, 2014; Trojelsgaard et al, 2015), which have shown that changes in plant composition and flower abundance, rather than changes in floral visitor composition, primarily influence the turnover of species interactions due to species turnover ( β ST ). However, our study revealed that the turnover of interactions can be explained by the turnover of both floral visitors and plants, driven by temperature dissimilarity across different elevations.…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis revealed that the primary driver of beta diversity of interactions was interaction turnover resulting from species turnover ( β ST ), rather than interaction rewiring ( β RW ). This finding is consistent with previous studies conducted on Mount Olympus in Greece (Minachilis et al, 2023) and other spatial gradients (Carstensen et al, 2014; Trojelsgaard et al, 2015), which have shown that changes in plant composition and flower abundance, rather than changes in floral visitor composition, primarily influence the turnover of species interactions due to species turnover ( β ST ). However, our study revealed that the turnover of interactions can be explained by the turnover of both floral visitors and plants, driven by temperature dissimilarity across different elevations.…”
Section: Discussionsupporting
confidence: 93%
“…Spatio‐temporal interaction β‐diversity is largely driven by species turnover. The high contribution of species turnover to spatial interaction β‐diversity is comparable to trends observed in other systems (Simanonok and Burkle 2014, Trøjelsgaard et al 2015, Minachilis et al 2023, Luna et al 2023) and suggests that rewiring of plant–pollinator interactions is not very common across space, possibly due to spatial abiotic gradients (Simanonok and Burkle 2014, Trøjelsgaard et al 2015) or dispersal boundaries (Trøjelsgaard et al 2015).…”
Section: Discussionsupporting
confidence: 75%
“…Plant-pollinator interactions in xeric longleaf pine savannas are highly variable across space and time, similar to other plant-pollinator systems (Simanonok and Burkle 2014, Trøjelsgaard et al 2015, CaraDonna et al 2017, Souza et al 2021, Luna et al 2023, Minachilis et al 2023). Spatiotemporal interaction β-diversity is largely driven by species turnover.…”
Section: Discussionmentioning
confidence: 81%
“…For instance, the disparate coevolution of species between islands may explain the observed high relevance of species turnover to structure at regional scale, as opposed to interaction rewiring. Similarly, recent studies also showed that high degree of endemism triggers turnover of species across space and elevation gradients [45,46]. In addition, the large distance between the closest islands (52 km) and the low dispersal ability of plants and insects suggest that dispersal limitation does not play a major role in species turnover between islands in the Canary region.…”
Section: Discussionmentioning
confidence: 87%